Leveraging Citizen Science in a College Classroom to Build Interest and Efficacy for Science and the Environment. (1st December 2021) - Smith, Haley; Allf, Bradley; Larson, Lincoln; Futch, Sara; Lundgren, Lisa; Pacifici, Lara; Cooper, Caren
University instructors can leverage citizen science resources to support student learning and cultivate interest and efficacy in science and the environment. In this case study, we examined learning outcomes of students from various majors participating in citizen science experiences as part of a general education science course at a large public university in the United States. In Spring 2019, students were assigned to collect arthropod data for an iNaturalist project. In Fall 2020, students chose between analyzing iNaturalist bumblebee observations or identifying plants using iNaturalist's Seek app. In both years, study participants completed pre- and post-assignment surveys designed to assess interest in nature, self-efficacy for environmental action, interest in science, and self-efficacy for learning and doing science (n2019 = 131, n2020 = 78). Across all students, we found a significant increase in interest in science and a slight increase in all other variables. Compared with agriculture and natural resources majors, non-majors reported greater increases for all variables, significantly so for efficacy for environmental action and efficacy for learning and doing science. Overall growth was also more pronounced in 2020 than 2019, with 2020 gains greatest among students who chose to analyze iNaturalist data. Our findings suggest that integrating choice and different ways of engaging with citizen science into university curricula has the potential to bolster interest and efficacy, which facilitate learning, particularly among students enrolled in courses outside their major. Designing citizen science assignments that incorporate choice and accommodate diverse student interests and motivations can help achieve these goals.